Enhanced insulin activity achieved in VDRa/b ablation zebrafish - Liu, Ruolan; Lu, Yao; Peng, Xuyan; Jia, Jingyi; Ruan, Yonglin; Shi, Shengchi; Shu, Tingting; Li, Tianhui; Jin, Xia; Zhai, Gang; He, Jiangyan; Lou, Qiyong; et al. (Frontiers in Endocrinology, 2023)
Introduction 1α,25-dihydroxyvitamin D3 (1α,25[OH]2VD3) is a hormone known for its key roles in calcium absorption and nutrient metabolism. In teleost fishes, 1α,25(OH)2VD3 insufficiency causes impaired glucose metabolism and lipid oxidation. However, the cascade and mechanisms of 1α,25(OH)2VD3 and the vitamin d receptor (VDR) signaling are unclear. Results In this study, two genes (vdra and vdrb) encoding paralogs of VDRs were genetically knocked out in zebrafish. Growth retardation and accumulated visceral adipose tissue have been observed in vdra-/-;vdrb-/- deficient line. In the liver elevated accumulation of triglycerides and suppressed lipid oxidation were detected. Morover significantly elevated 1α,25(OH)2VD3 levels were detected in vdra-/-;vdrb-/- zebrafish due to cyp24a1 transcription repression. Furthermore VDRs ablation Enhanced insulin signaling including elevated insulin/insra trancriptional levels, glycolysis, lipogenesis and promoted AKT/mTOR activity. Discussion In conclusion, our present studies provides a zebrafish model with an elevated 1α,25(OH)2VD3 levels in vivo. The 1α,25(OH)2VD3/VDRs signaling promote lipid oxidation activity. However 1α,25(OH)2VD3 activity of regulation of glucose homeostasis through Insulin/Insr was independent of nuclear VDRs in teleosts.